Análise clínica, imunológica e microbiológica da associação entre periodontite e COVID- 19: um estudo caso-controle - Larissa Marques Bemquerer (2022)
This study investigated the clinical, immunological, and microbiological parameters in individuals with coronavirus disease (COVID-19) and controls, exploring if periodontitis-driven inflammation contributes to the occurrence and severity of COVID19 endpoints. Case [positive reverse transcriptase- polymerase chain reaction (RTPCR) for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)] and control (negative RT-PCR for SARS-CoV-2) individuals underwent clinical and periodontal assessment. Salivary levels of tumoral necrosis factor alpha, interleukin (IL)-6, IL-1β, IL-10, osteoprotegerin, receptor activator of nuclear factor Kappa-B (RANKL), neutrophil extracellular traps, and subgingival biofilm were analysed at two time-points. Data on COVID-19-related outcomes and comorbidity information were assessed from medical records. Ninety-nine cases of COVID-19 and 182 controls were included for analysis. Periodontitis was associated with more hospitalization (p=0.009), more days in the intensive care unit (ICU) (p=0.042), admission to the semi-ICU (p=0.047), and greater need for oxygen therapy (p=0.042). After adjustment for confounders, periodontitis resulted in a 1.13-fold increase in the chance of hospitalization. Salivary IL-6 levels (p=0.010) were increased in individuals with COVID-19 and periodontitis. Periodontitis was associated with increased RANKL and IL-1β after the end of COVID19 infection. No significant changes were observed in bacterial loads of the periodontopathogens Porphyromona gingivalis, Aggregatibacter actinomycetemcomitans, Tanerella forsythia, and Treponema denticola during and after the infection. Periodontitis was associated with worse outcomes from COVID-19 (hospitalization, use of oxygen, days at ICU and admission to semi-ICU), suggesting the relevance of periodontal care to reduce the burden of overall inflammation. Understanding the crosstalk between SARS-CoV-2 infection and chronic conditions such as periodontitis that can influence the disease outcome is important to potentially prevent complications of COVID-19